The Evaluation of Mechanical Properties of High-tin Bronzes - Nadolski M. (Archives of Foundry Engineering, 2017)
High-tin bronzes are used for church bells and concert bells (carillons). Therefore, beside their decorative value, they should also offer other functional properties, including their permanence and good quality of sound. The latter is highly influenced by the structure of bell material, i.e. mostly by the presence of internal porosity which interferes with vibration of the bell waist and rim, and therefore should be eliminated. The presented investigations concerning the influence of tin content ranging from 20 to 24 wt% on mechanical properties of high-tin bronzes allowed to prove the increase in hardness of these alloys with simultaneous decrease in the tensile and the impact strengths (Rm and KV, respectively) for the increased tin content. Fractures of examined specimens, their porosity and microstructures were also assessed to explain the observed regularities. A reason of the change in the values of mechanical properties was revealed to be the change in the shape of α-phase crystals from dendritic to acicular one, and generation of grain structure related to the increased Sn content in the alloy.